The factor that influences sleep quality among students’ universiti malaysia kelantan, city campus - Kogila A/P Murugan; Nur Fatiehah Natasya Syamsul; Che Muhammad Danial Che Ibrahim; Nur Rindiani Munaya Nazran (2023)
The purpose of this study is to review the factors that influence the sleep quality among students at University Malaysia Kelantan, City Campus. The factors that influence sleep quality among students at University Malaysia Kelantan, City Campus are lifestyle, mental health, social factors, and physical factors. A cross- sectional study was conducted among students from Faculty of Hospitality, Tourism and Wellness (FHPK) at University Malaysia Kelantan, City Campus. The sociodemographic data were obtained from a simple random sampling that took 365 respondents, age range from 18 to 30 years and above, including both genders. All participants completed six sections of questionnaires. Questionnaires was evaluated to identify the quality of sleep among students of University Malaysia Kelantan, City campus. Analyses were conducted with Statistical Package Social Sciences (SPSS) version 26. There are many studies that have been identified to be classified according to investigating factors of sleep quality. Physical factors and lifestyle are healthy factors that improve sleep quality, while mental health and social factors reduce sleep quality. University students are exposed to different risk factors for sleep quality. Keywords: Sleep Quality, Lifestyle, Mental Health, Social, and Physical Factors